IMPACT OF INTERMETALLIC PHASES ON THE ALUMINIUM ALLOYS EROSION RESISTANCE - Ostrovska, A. E.; Volchok, I. P. (Science and Transport Progress, 2010)
Investigation of the influence of intermetallic phases on the mechanism of fatigue fracture of the secondary aluminum alloys was made.